2018
DOI: 10.1016/j.ekir.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Plasminogen Activator Receptor (suPAR) and All-Cause and Cardiovascular Mortality in Diverse Hemodialysis Patients

Abstract: IntroductionThe soluble receptor of urokinase plasminogen activator (suPAR) is an innate immunity/inflammation biomarker predicting cardiovascular (CV) and non-CV events in various conditions, including type 2 diabetic patients on dialysis. However, the relationship between suPAR and clinical outcomes in the hemodialysis population at large has not been tested.MethodsWe measured plasma suPAR levels (R&D enzyme-linked immunosorbent assay [ELISA]) in 1038 hemodialysis patients with a follow-up of 2.9 years (inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…In our data, dialysis vintage was signi cantly correlated to suPAR levels prior to transplantation (p = 0.013, r = 0.258). In congruence, among other factors, dialysis vintage as well as the age of the patient have recently been linked to the suPAR levels in dialysis patients [11], [12]. After KTx, the suPAR levels decreased to a comparable level at the one-year mark (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our data, dialysis vintage was signi cantly correlated to suPAR levels prior to transplantation (p = 0.013, r = 0.258). In congruence, among other factors, dialysis vintage as well as the age of the patient have recently been linked to the suPAR levels in dialysis patients [11], [12]. After KTx, the suPAR levels decreased to a comparable level at the one-year mark (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, morbidity and mortality of DD recipients are usually higher that is perhaps related to longer dialysis vintage [23], [24]. Notably, Torino and Drechsler et al demonstrated that higher suPAR levels even translated into all-cause and both CVD and non-CVD mortality in hemodialysis patients [11], [12].…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 24 , 26 , 32 , 33 , 45 Furthermore, it is considered a marker and may be a predictor of outcomes in a variety of cardiovascular diseases associated with inflammation. 1 , 14 , 17 , 22 , 32 , 41 , 47 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Serum suPAR was measured by enzyme immunoassay from R&D Systems (DUP00; Minneapolis, MN) as described previously. 54 The samples were diluted 5-fold before assay and assayed in duplicate. The sensitivity of the assay without dilution of the serum is <33 pg/mL, which translates to <0.2 ng/mL with the 5-fold dilution of serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation